A hybrid system for the overproduction of complex ergot alkaloid chanoclavine - Ma, Yaqing; Yan, Juzhang; Yang, Lujia; Yao, Yongpeng; Wang, Luoyi; Gao, Shu-Shan; Cui, Chengsen (Frontiers in Bioengineering and Biotechnology, 2022)
Synthetic biology-based methods (Sbio) and chemical synthesis (Csyn) are two independent approaches that are both widely used for synthesizing biomolecules. In the current study, two systems were combined for the overproduction of chanoclavine (CC), a structurally complex ergot alkaloid. The whole synthetic pathway for CC was split into three sections: enzymatic synthesis of 4-Br-Trp (4-Bromo-trptophan) using cell-lysate catalysis (CLC), chemical synthesis of prechanoclavine (PCC) from 4-Br-Trp, and overproduction CC from PCC using a whole-cell catalysis (WCC) platform. The final titer of the CC is over 3g/L in this Sbio-Csyn hybrid system, the highest yield reported so far, to the best of our knowledge. The development of such a combined route could potentially avoid the limitations of both Sbio and Csyn systems and boost the overproduction of complex natural products.